The search of biologically active compounds in a row of 8-amino-7-(2-hydroxy-2-phenylethyl)-3-methylxanthines - Ivanchenko, D. H.; Romanenko, M. I.; Bilenkyi, S. A.; Іванченко, Дмитро Григорович; Романенко, Микола Іванович; Біленький, Сергій Андрійович (My University, 2016)
The aim of the work was the synthesis of 8-aminoderivatives of 7-(2-hydroxy-2-phenylethyl)-3-methylxanthine previously undescribed and the study of their antioxidant, antimicrobial and antifungal activity.
Keywords: фармацевтична хімія; xanthine; organic synthesis; antimicrobial activity; antifungal activity; antioxidant activity